2000
DOI: 10.1021/bp9901318
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Microcarrier Adhesion to Gas‐Liquid Interfaces and Foam

Abstract: The interaction of microcarriers, both with and without cells attached, with gas bubbles was studied. These studies consisted of qualitative microscopic observations of microcarriers with bubbles, quantitative measurements of microcarrier entrapment in foam, and quantitative measurements of the effect of bubble rupture at gas-medium interfaces. Ten different "protective additives" were evaluated for their ability to change the dynamic surface tension of the culture media and to prevent microcarrier adhesion to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In a bioreactor, hydrodynamic force generated from bubble rupture contributes significant damage to cells that are either attached or nearby the bubbles . The addition of poloxamer 188 can lower the liquid surface tension thereby reducing the force during bubble rupture and decreasing cell‐to‐bubble attachment which is thermodynamically favorable without surfactant . Cell–bubble induction time also increased substantially with the use of poloxamer 188, indicating that it takes a longer time for cell‐to‐bubble attachment to occur .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a bioreactor, hydrodynamic force generated from bubble rupture contributes significant damage to cells that are either attached or nearby the bubbles . The addition of poloxamer 188 can lower the liquid surface tension thereby reducing the force during bubble rupture and decreasing cell‐to‐bubble attachment which is thermodynamically favorable without surfactant . Cell–bubble induction time also increased substantially with the use of poloxamer 188, indicating that it takes a longer time for cell‐to‐bubble attachment to occur .…”
Section: Introductionmentioning
confidence: 99%
“…19 The addition of poloxamer 188 can lower the liquid surface tension thereby reducing the force during bubble rupture and decreasing cell-to-bubble attachment which is thermodynamically favorable without surfactant. [20][21][22] Cell-bubble induction time also increased substantially with the use of poloxamer 188, indicating that it takes a longer time for cell-to-bubble attachment to occur. 23 Ma et al employed a bubble collector under different poloxamer 188 concentrations and cell densities to quantitatively show the decrease of cell-to-bubble attachment.…”
Section: Introductionmentioning
confidence: 99%
“…Two issues of concern have been documented in the use of microcarrier culture. The first is hydrodynamic shear from stirring and/or sparging (3133); the second is oxygen limitation, particularly with macroporous microcarriers (34). Mufti and Shuler (26) demonstrated that Hep G2 cells grown on microcarriers induce a specific cytochrome P‐450 monooxygenase, a marker of cellular stress even at relatively low agitation rates.…”
Section: Introductionmentioning
confidence: 99%
“…Visual observations and corelational studies of the foam layer, with and without PF-68, indicate that cells are still present in the liquid in between the bubbles (Bauer et al, 2000;Hu et al, 2007;Ma et al, 2004). In general, as bubble sizes get smaller, the foam tends to be more stable, thicker, and the relative amount of liquid retained in the fluid between bubbles becomes greater for a given amount of gas sparged.…”
Section: Discussionmentioning
confidence: 99%